A+ guide to managing and maintaining your pc with lab exercises: hardware - Andrews, Jean; Dark, Joy ;Verge, Todd (Singapore : Cengage Learning Asia Pte Ltd, 2015)
This lab manual is designed to be the best tool on the market to enable you get the hands-on practical experience you need to learn to troubleshoot and repair personal computers and operating system.
Chapter 1. First look at computer parts and tools -- Chapter 2. Working inside a computer -- Chapter 3.All about motherboards -- Chapter 4. Supporting Processors and Memory -- Chapter 5. Supporting Hard Drives -- Chapter 6. Supporting I/O and Storage Devices -- Chapter 7. Troubleshooting Hardware Problems -- Chapter 8. Supporting I/0 and storage devices -- Chapter 9. Satisfying Customer needs -- Chapter 10.Maintaining Windows -- Chapter 11, Optimizing Windows -- Chapter 12. Troubleshooting and Applications -- Chapter 13. Troubleshooting Hardware Problems.